2020
DOI: 10.1111/tbed.13531
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogenetic characterization of bovine ephemeral fever virus (BEFV) of Middle Eastern lineage associated with 2018‐2019 outbreaks in India

Abstract: Bovine ephemeral fever virus (BEFV) is an evolving arbovirus reported across tropical, subtropical and temperate climatic zones globally. This study reveals prominent BEFV outbreaks in India, emerging annually during monsoons in subtropical areas accompanied by a congenial abundance of the vector population. PCR‐based detection of viral genomic RNA in the blood samples collected during outbreaks of 2018–2019 for the first time confirmed the presence of BEFV in India. Phylogenetic analysis based on the glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Intriguingly, sequence and phylogenetic analysis revealed a close relatedness to Israeli and Turkish isolates, implying a common origin. The branching patterns coincide with the previous P and G genes based phylogenetic analysis, projecting its relative high pathogenicity (Yeruham et al 2010 ; Abayli et al 2017 ; Pyasi et al 2020 ). Interestingly, no significant correlation between genotypes and geographical distance was observed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Intriguingly, sequence and phylogenetic analysis revealed a close relatedness to Israeli and Turkish isolates, implying a common origin. The branching patterns coincide with the previous P and G genes based phylogenetic analysis, projecting its relative high pathogenicity (Yeruham et al 2010 ; Abayli et al 2017 ; Pyasi et al 2020 ). Interestingly, no significant correlation between genotypes and geographical distance was observed.…”
Section: Discussionsupporting
confidence: 84%
“…The new geographical expansions with enhanced case fatality rate and high production losses alarm BEFV as an evolving arbovirus that warrants closer scrutiny in surveillance, epidemiology, and ecological impact (Lee 2019 ; Yanase et al 2020 ). Despite the multiple decades of episodic reporting on seasonal incursions from many South Asian countries, including India (Nandi and Negi 1999 ; Walker and Klement 2015 ), no complete sequence information was available until recently (Pyasi et al 2020 ), which hinders progress for its detection and prevention. Field detection solely relies on the observed clinical signs accompanied by haemato-biochemical analysis in the lack of any serological diagnostics kits.…”
Section: Introductionmentioning
confidence: 99%
“…BEFV is considered endemic and known to cause an epizootic disease in many regions, such as East Asia [45], Japan [19,24], China [16,27], the Philippines [28], Thailand [6], Taiwan [21,31,44], Australia [15,17], India [38], Israel [11,47], Jordan [20], Iran [3,5], Kingdom of Saudi Arabia [50], South Africa [37], and Turkey [9,36]. For example, previous studies performed in Australian deer reported serological evidence for BEFV in red deer [12] and another study conducted in Australia demonstrated that all samples screened in wild deer were PCR-negative for BEFV, although BEFV is endemic in Australia [22].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine Ephemeral Fever (BEF) is an economically important disease that occurs in tropical and subtropical areas of Africa, the Middle East, Asia and Australia (Walker & Klement, 2015). The causative virus is classified in the genus Ephemerovirus within the Rhabdoviridae family (Pyasi et al., 2020). It is transmitted through several vector species including Culicoides and mosquitoes and it causes an acute inflammatory disease in cattle and water buffalo (Bakhshesh & Abdollahi, 2015; Cybinski et al., 1990; Pyasi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The causative virus is classified in the genus Ephemerovirus within the Rhabdoviridae family (Pyasi et al., 2020). It is transmitted through several vector species including Culicoides and mosquitoes and it causes an acute inflammatory disease in cattle and water buffalo (Bakhshesh & Abdollahi, 2015; Cybinski et al., 1990; Pyasi et al., 2020). BEF disease negatively impacts the beef and dairy industry through reduced milk production, infertility and abortions in late‐pregnancy (Bakhshesh & Abdollahi, 2015; Gao et al., 2017).…”
Section: Introductionmentioning
confidence: 99%